Use of Fintech for Payment: Approach to Technology Acceptance Model Modified - Ardhya Yudistira Adi Nanggala (Perkumpulan Praktisi Akuntansi Indonesia, 2020)
This study examined the effect of two main perceptions on TAM models along with web security perceptions of the attitudes and intention to use fintech. Web security perceptions are considered as additional variables are important in influencing attitudes and intention to use of fintech because users will use information systems. Sample was selected by the snowball method. Fintech usage questionnaire was developed using existing scales from prior tam instruments and modified where appropriate. 147 participants completed the survey questionnaire measuring their responses to perceived usefulness, perceived ease of use, attitudes towards usage and behavioral intention to use. The results showed that the variable perception of the usefulness of a positive influence on the attitude of the use of fintech, perceived security web effect on the attitude of the use of fintech and attitudes towards usage influence intention to use of fintech. The perceived ease of use and the perceived ease of use are not significant effect on the perception of the use of fintech.